2022
DOI: 10.3390/membranes12080732
|View full text |Cite
|
Sign up to set email alerts
|

Ag/ZnO Thin Film Nanocomposite Membrane Prepared by Laser-Assisted Method for Catalytic Degradation of 4-Nitrophenol

Abstract: Zinc oxide thin film (ZnO thin film) and a silver-doped zinc oxide nanocomposite thin film (Ag/ZnO thin film) were prepared by the technique of the pulsed laser deposition at 600 °C to be applicable as a portable catalytic material for the removal of 4-nitrophenol. The nanocomposite was prepared by making the deposition of the two targets (Zn and Ag), and it was analyzed by different techniques. According to the XRD pattern, the hexagonal wurtzite crystalline form of Ag-doped ZnO NPs suggested that the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The integration of Ag nanostructures in ZnO, which exploits the surface plasmon resonance phenomenon induced by them, has been widely employed to enhance the intrinsic properties of ZnO. Numerous studies have reported that Ag/ZnO nanocomposites demonstrate improved optical and electronic properties, suggesting their potential for use in photocatalysis [23,[26][27][28][29][30], sensing [31][32][33][34], solar cells [35,36], optoelectronics [26,[37][38][39] and antimicrobial [40,41], antibacterial [42] and anticancer [43,44] applications. Clearly, diverse fabrication methods apply to this nanocomposite, as previously outlined in the references for net ZnO and noble metallic NP synthesis, as well as described in [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of Ag nanostructures in ZnO, which exploits the surface plasmon resonance phenomenon induced by them, has been widely employed to enhance the intrinsic properties of ZnO. Numerous studies have reported that Ag/ZnO nanocomposites demonstrate improved optical and electronic properties, suggesting their potential for use in photocatalysis [23,[26][27][28][29][30], sensing [31][32][33][34], solar cells [35,36], optoelectronics [26,[37][38][39] and antimicrobial [40,41], antibacterial [42] and anticancer [43,44] applications. Clearly, diverse fabrication methods apply to this nanocomposite, as previously outlined in the references for net ZnO and noble metallic NP synthesis, as well as described in [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the wide band gap restricts the catalytic activity due to the low light absorption, to conquer this issue the band gap of ZnO can be tuned by ion doping or coupling with different semiconductors, deposition metals and non-metals, defect Engineering and co-catalyst will regulate the band gap energy 21 , 22 . Multiple studies have been reported on ZnO combinational catalysts such as NiS/ZnO 23 , CuO/ZnO 24 , Ni/rGO 25 , Ag/ZnO 26 28 , ZnO 29 , graphene-ZnO 30 , 31 , Co–ZnO 32 for the PNP reduction reaction. Recently, Bekru et al, reported the (rGO–ZnO)/CuO nanocomposite interface is a highly efficient photo-catalyst for PNP reduction 33 .…”
Section: Introductionmentioning
confidence: 99%